Experimental and Numerical Investigation of the Discharge Valve Limiter Geometric Features Change on Compressor Thermal Efficiency - Ekemen, A.; Pinarbasi, A.; Sahin, C.; Yildirim, A. (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
The incorporation of inverter technology into hermetic reciprocating compressors has led to a significant decrease in energy consumption. However, to ensure efficient operation of the compressor components at varying rotation speeds, new optimizations are required. Discharge valves are one of the components most affected by high and low rotational speeds. Since the opening forces on the valves are high at high rotational speeds, they open and close properly, while flutter movements occur at lower rotational speeds. These flutter movements increase the discharge losses. Therefore, the movements of the discharge valves and the geometric features of the limiter, which restricts valve movement, play crucial roles in determining the discharge line losses and overall compressor efficiency. Variables such as the forces acting on the valve and the mass flow area are closely related with the maximum displacement of the discharge valve limited by the limiter. This study aims to prevent flutter movements and increase hermetic reciprocating compressor used in refrigerators efficiency by modifying the limiter geometric features. The results in working conditions of different condensation and evaporation temperatures at different rotation speeds, which were examined experimentally and numerically, are shared. Additionally, by utilizing a 1-D model solver, the compressor's efficiency is analyzed parametrically. The results indicate that reducing the limiter distance yields better outcomes at low rotation speeds in the higher compression ratio condition compared to lower compression ratio conditions and higher rotation speeds.
Keywords: Reciprocating compressor; Discharge valves; Limiter; P-V diagrams; Valve displacement; Engineering